Effect of Eriobotrya japonica L. (Chinese medicinal plant) on the regulation of lipid metabolism in atherosclerosis-induced mice and in HepG-2 cells - Imane Mokhtari; Dragan Milenkovic; Souliman Amrani; Hicham Harnafi (Elsevier, 2024)
Background: Hyperlipidemia and related metabolic disorders are the main cause of nonalcoholic fatty liver diseases, atherosclerosis and cardiovascular complications. Loquat (Eriobotrya japonica) leaf infusion is an innovative formula derived from Traditional Chinese medicine, known for its therapeutic properties against a number of ailments including inflammation, diabetes and hyperlipidemia. Aim of the study: This study was designed to identify the active compounds of an aqueous extract of E. japonica leaves (ELE) and to investigate its effect on hyperlipidemia and related metabolic complications in high-fat high-sucrose diet-fed mice as well as to elucidate the possible underlying mechanisms. Materials and Methods: Mice were fed a high-fat high-sucrose diet for 3 months and treated with the ELE at doses of 50 mg/kg and 100 mg/kg. Lipids in plasma, liver, adipose tissue, bile and feces were quantified using enzymatic kits. Liver steatosis and oxidative status were highlighted by measuring AST, ALT, ALP, MDA, SOD and catalase activities as well as monitoring of lipid droplets in histological sections. The identification and quantification of possible active compounds were carried out using the HPLC-DAD method. The underlying mechanisms were predicted by in silico study and confirmed by quantifying the expression of the principal involved proteins including PCSK-9, CYP7A1 and p-AMPK in HepG2 cells. Results: The ELE restored lipid metabolism and improved liver histological structures. It also reduced oxidative stress by lowering MDA levels and activating SOD and catalase enzymes. The ELE prevented hepatic steatosis and corrected transaminases profile. HPLC analysis reveals seven phenolic compounds, with ferulic acid being the major one. The extract and its identified phenolic compounds upregulated the expression of CYP7A1 and p-AMPK while downregulated the expression of PCSK-9 in HepG2 cells. The ELE appears to be nontoxic in mice (LD50>5000 mg/kg) and in HepG2 cells at pharmacologically active doses. Conclusion: the ELE could be considered as a source of active biomolecules to produce phytotherapeutics drugs or dietary supplements to treat hyperlipidemia and related cardio-metabolic diseases.